The unexpected guest : a mystery - Osborne, Charles, 1927-2017.; Christie, Agatha, 1890-1976. (New York : St. Martin's Minotaur, 1952)
A motorist whose car broke down seeks assistance in a nearby house, only to find its owner shot in a wheelchair. When the wife confesses, he offers to help cover the crime. A novelization of a play.
Keywords: Murder -- Scotland -- Fiction; Mystery fiction